Using Infographics to Help Students Understand Descriptive Texts Better - David Hermawan; Margana Margana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
This study aims to (1) examine how the use of infographic media improves the reading comprehension of eighth-grade students in descriptive texts at SMPN 1 Dusun Selatan, and (2) explore the process and behavioral changes that accompany the improvement in students’ reading comprehension after the implementation of infographic media. The study utilized the Classroom Action Research (CAR) method, following the model proposed by Mills (2018), with two observation cycles consisting of planning, implementation, observation, and reflection. Data were collected through pre-test and post-test reading comprehension assessments, interviews, questionnaires, and photographs. The reading comprehension ability was evaluated based on the Kriteria Ketuntasan Minimal (KKM), with the goal of achieving scores above the minimum mastery threshold. Quantitative data were analyzed using statistical methods, while qualitative data were analyzed descriptively and triangulated to ensure validity and reliability. The findings show significant improvements in students' reading comprehension after the use of infographic media. The average post-test score increased by 35%, and the percentage of students meeting the KKM rose from 48% in the pre-test to 84% in the post-test. Additionally, students exhibited positive changes in their behavior, becoming more engaged, active, and confident in their learning. They showed a greater ability to focus on interpreting texts and expressed less anxiety when faced with descriptive texts. This study concludes that infographic media effectively enhances reading comprehension and fosters behavioral changes, such as increased student engagement and confidence, which ultimately improves learning outcomes.